The recent financial crisis, start‐up financing and survival. (19th June 2018) - Deloof, Marc; Vanacker, Tom
Abstract: We investigate the effects of the recent financial crisis on start‐up financing and survival using a dataset that covers all Belgian new business registrations between 2006 and 2009. We find that bank debt is the single most important source of funding, even for start‐ups founded during the crisis. However, start‐ups founded in crisis years use less bank debt and have a higher likelihood of bankruptcy, even after controlling for their creditworthiness. These effects are stronger for start‐ups that are more dependent on bank debt, such as start‐ups founded in bank dependent industries and start‐ups founded by entrepreneurs who are more likely to be financially constrained.